(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud Computing is solution in which resources such as hardware, software, network and storage requirement are provided to the user as per the demand. Basically Cloud Computing is the combination of private cloud and public cloud. This paper focus the overview of security issued which may arise during file sharing while adopting the hybrid clouds. It also focuses to use Federated Key Management in the cloud such that each user and each server will have its own unique identity, and the identity is allocated by the system hierarchy.